2008
DOI: 10.1108/17506200810861258
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and co‐leadership in ethnic enterprises in Canada

Abstract: PurposeTo identify the influence of ethnicity and ethnic social capital on entrepreneurial practices such as the co‐direction of a firm, and more particularly on aspects of venture creation, management, and business development.Design/methodology/approachThe research was based on a field survey carried out in the cities of Montreal, Toronto, and Vancouver. The authors study the entrepreneurs who had partners in their firms. The sampling technique, known as “snowball sampling,” did not concentrate specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
10
1
1
Order By: Relevance
“…This study shows little difference between immigrant and non-immigrant entrepreneurs in terms of where they seek information and advice, or whether they consider coethnic employees as important. These findings contradict earlier research on immigrant entrepreneurship in major gateway cities which identified networks of coethnic ties as instrumental in successfully establishing and running their businesses (e.g., Brenner et al 2010;Lin 2007;Paré et al 2008;van Delft, Gorter, and Nijkamp 2000;Zhou and Cho 2010). So, unlike large cities with diverse and numerous immigrants, the "ethnic factor" plays only a minor role in Kelowna's small-and medium-sized immigrant businesses.…”
Section: Discussion Of Findingscontrasting
confidence: 93%
See 3 more Smart Citations
“…This study shows little difference between immigrant and non-immigrant entrepreneurs in terms of where they seek information and advice, or whether they consider coethnic employees as important. These findings contradict earlier research on immigrant entrepreneurship in major gateway cities which identified networks of coethnic ties as instrumental in successfully establishing and running their businesses (e.g., Brenner et al 2010;Lin 2007;Paré et al 2008;van Delft, Gorter, and Nijkamp 2000;Zhou and Cho 2010). So, unlike large cities with diverse and numerous immigrants, the "ethnic factor" plays only a minor role in Kelowna's small-and medium-sized immigrant businesses.…”
Section: Discussion Of Findingscontrasting
confidence: 93%
“…Business owners obtain information and advice from various sources, including their families and relatives, and their network of contacts from inside or outside their ethnic circle. The literature on immigrant entrepreneurship asserts the importance of coethnic friends and organizations as information sources (Brenner et al 2010;Chan and Cheung 1985;Deakens et al 2007;Galbraith, Rodriguez, and Stiles 2007;Lin 2007;Marger 1989;Paré et al 2008;Teixeira 2001;Teixeira, Lo, and Truelove 2007;van Delft, Gorter, and Nijkamp 2000;Waldinger 1986;Zhou and Cho 2010). Our study reveals little difference between immigrant and non-immigrant entrepreneurs in terms of where they seek information and advice.…”
Section: Barriers To Business Development As Experienced By a Samplementioning
confidence: 58%
See 2 more Smart Citations
“…Des études plus spécifiques ont été menées par Paré et al . (2008) sur cet aspect de co-leadership qui implique un système de collaboration et de complémentarité où les responsabilités managériales sont partagées .…”
Section: L'entrepreneuriat Féminin Dans Un Contexte De Développement unclassified